2014
DOI: 10.1021/ja412996f
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo- and Enantioselective Addition of Anilide-Functionalized Allenoates toN-Acylimines Catalyzed by a Pyridylalanine-Based Peptide

Abstract: A selective peptide-catalyzed addition of allenic esters to N-acylimines is reported. Tetrasubstituted allenes were achieved with up to 42:1 diastereomeric ratio and 94:6 enantiomeric ratio (up to 99:1 er after recrystallization of the major diastereomer). An exploration of the role of individual amino acids within the peptide was undertaken. The scope of the reaction was explored and revealed heightened reactivity with thioester-containing allenes. A mechanistic framework that may account for the observed rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(53 citation statements)
references
References 44 publications
1
51
1
Order By: Relevance
“…We reported that these cyclic amino acid-containing L-Leu-based peptides induced right-handed (P) α-helical structures. Furthermore, the cyclic amino acid-containing L-amino acid-based heteropeptides may be used as chiral organocatalysts [13][14][15] and cell-penetrating peptides. [16][17][18][19] We previously reported the synthesis of a chiral five-membered carbocyclic ring dAA: (R)-or (S)-amino-3,3-(ethylenedioxy)cyclopentanecarboxylic acid (Ac 5 c 3EG ) with an ethylene acetal moiety, in which the α-carbon atom was a chiral center, and the helical structures of its homo-chiral homopeptides.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that these cyclic amino acid-containing L-Leu-based peptides induced right-handed (P) α-helical structures. Furthermore, the cyclic amino acid-containing L-amino acid-based heteropeptides may be used as chiral organocatalysts [13][14][15] and cell-penetrating peptides. [16][17][18][19] We previously reported the synthesis of a chiral five-membered carbocyclic ring dAA: (R)-or (S)-amino-3,3-(ethylenedioxy)cyclopentanecarboxylic acid (Ac 5 c 3EG ) with an ethylene acetal moiety, in which the α-carbon atom was a chiral center, and the helical structures of its homo-chiral homopeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Using identical conditions from Table 1, entry 8b ut with an additional phenylalanine at i + 2( P9) resulted in higher yield, but only am arginal decrease in enantioselectivity (Table 1, entry 9). Considering our hypothesis regarding p-p interactions,w ei ncorporated naphthylalanine (Nal;T able 1, entries [10][11][12] and O-benzyltyrosine (Table 1, entry 13) at i + 3. Retaining the C-terminal dimethylamide (Scheme 4, entries 10-13), we found that P10 provided the highest enantioselectivity observed thus far with 92:8 e.r.…”
mentioning
confidence: 97%
“…Herein, we present our work on the first peptidecatalyzed, [11] atroposelective carbon-carbon bond-forming reaction between two independent fragments,a ne ster-bearing quinone and an aphthol, to yield non-C 2 -symmetric BINOL-type scaffolds. [12] Notably,related to the pioneering work of the Tangroup and Salvio,B ella, and co-workers, [9,10] few other examples exist for the organocatalyzed construction of non-C 2 -symmetric BINOL-type catalysts or ligands with substituents decorating the backbone,afeature that often imparts high enantioselectivity. [13] Important examples include the 3,3'disubstituted BINOL carboxylic acids developed by Te rada and co-workers for hetero-Diels-Alder reactions, [14] H 8 -BINOL-CPAs developed by Krische and co-workers for the enantioselective CÀHc rotylation of alcohols, [15] and approaches to preparing racemic NOBIN-and BINOL-type biaryls by Gao et al and Kamitanaka et al using quinone monoacetals as coupling partners.…”
mentioning
confidence: 99%
“…We initially employed an isoindigo with an N-Boc group,and while the reactions went to completion within am inute and the desired (3+ +2) annulation products were formed in high yields,t he stereoselectivities of the reaction were less satisfactory.W es ubsequently chose al ess reactive isoindigo 1afor further studies.T oour delight, l-Thrderived phosphine-amide catalysts displayed remarkable catalytic effects,a ffording the spirobisoxindole 3a in high chemical yield and with good enantioselectivity.T he best catalyst was the O-TBDPS-l-Thr-derived P4, [12] furnishing the desired 3a in 94 %y ield and 92 % ee within 15 minutes (entry 4). [13] With the optimal reaction conditions in hand, we subsequently proceeded to establish the scope of the reaction (Scheme 3). Solvent screening then followed.…”
mentioning
confidence: 99%
“…Moreover, g-benzyl-substituted benzyl allenoate was also tested, and was found to be unreactive. [13] With the optimal reaction conditions in hand, we subsequently proceeded to establish the scope of the reaction (Scheme 3). To allow flexibility in the subsequent structural manipulations of the bisoxindole annulation products,w e examined isoindigos with either an N-methyl or N-allyl group, and the corresponding annulation products were obtained in excellent yields and ee values (3b and 3c).…”
mentioning
confidence: 99%